Evaluating the reliability and validity of a Chinese version of the performance-oriented mobility assessment among patients with chronic stroke - Zhong, Ming; Jing, Yongnan; Zhao, Xiaofeng; Gao, Ying; Jiang, Yanju; Liu, Yihao; Du, Chunping (Frontiers in Neurology, 2024)
BackgroundThe Performance-Oriented Mobility Assessment (POMA) is a reliable instrument for evaluating the mobility (balance and gait) of patients with chronic stroke to manage their risk of falling; however, it has not been validated among Chinese patients with stroke. This study aimed to evaluate the reliability and validity of the Chinese POMA in patients with stroke.MethodsThe POMA was applied to volunteer patients with stroke from the Shanghai MCC Hospital. The patients underwent the Chinese POMA, Berg balance scale (BBS), and timed up and go (TUG) tests on the first day of inpatient treatment. The same physician repeated the tests the next day to assess test–retest reliability, and upon the patient’s discharge from the inpatient department, two different physicians measured inter-rater reliability.ResultsThe study involved 76 patients with stroke (age: 62.04 ± 9.76 years; 34.2% female). The results showed that the Chinese POMA had good overall internal consistency (σ=. 875), with a moderate consistency between its two subscales (balance σ = 0.875; gait σ = 0.668). The individual items showed high test–retest (ICC = 0.997) and inter-rater reliability (ICC = 0.988). The content validity test showed high correlations between the Chinese POMA, the BBS (rs = 0.70), and the TUG (rs = −0.75). However, the confirmatory factor analysis suggested that the two-factor model (balance and gait) was mediocre.ConclusionThe Chinese POMA showed acceptable reliability and validity for evaluating mobility (balance and gait) in Chinese patients with stroke in terms of their risk of falling. However, further evaluation of the two-factor model (balance and gait) is required.